In Vitro Interactions between Okadaic Acid and Rat Gut Microbiome - Yang Liu; Siyuan Xu; Qiudie Cai; Dawei Li; Hongye Li; Weidong Yang (Marine Drugs, 2022)
Okadaic acid (OA) is a marine biotoxin associated with diarrhetic shellfish poisoning (DSP), posing some threat to human beings. The oral toxicity of OA is complex, and the mechanism of toxicity is not clear. The interaction between OA and gut microbiota may provide a reasonable explanation for the complex toxicity of OA. Due to the complex environment in vivo, an in vitro study may be better for the interactions between OA and gut microbiome. Here, we conducted an in vitro fermentation experiment of gut bacteria in the presence of 0–1000 nM OA. The remolding ability of OA on bacterial composition was investigated by 16S rDNA sequencing, and differential metabolites in fermentation system with different concentration of OA was detected by LC-MS/MS. We found that OA inhibited some specific bacterial genera but promoted others. In addition, eight possible metabolites of OA, including dinophysistoxin-2 (DTX-2), were detected in the fermentation system. The abundance of Faecalitalea was strongly correlated with the possible metabolites of OA, suggesting that Faecalitalea may be involved in the metabolism of OA in vitro. Our findings confirmed the direct interaction between OA and gut bacteria, which helps to reveal the metabolic process of OA and provide valuable evidence for elucidating the complex toxicity of OA.